A novel approach to represent the energy system in integrated assessment models. (1st November 2022) - Parrado-Hernando, Gonzalo; Pfeifer, Antun; Frechoso, Fernando; Miguel González, Luis Javier; Duić, Neven
Abstract: The Spanish national energy and climate plan (PNIEC) has recently been published, leading the worldwide task of climate change mitigation towards a net zero-carbon economy by 2050. The objective scenario of the PNIEC expects to reach a renewable share in the power system of 74% by 2030. In this context, three contributions are developed: i) providing an analysis of how Spain is facing the energy transition; ii) conceptualizing the link between an hourly energy model (EnergyPLAN) and a yearly integrated assessment model (MEDEAS); and iii) proposing a transparent policy agenda for the Spanish benchmarking in line with the official report. The results clarify the decreasing role such technologies as the combined heat and power facilities, as well as the pressure of biomass in Spain. Coherency in translating common variables in the energy chain of IAMs to the energy model is effectively reflected in the tables as an output of the research. Positive conclusions are found for Spain. The commitment of 74% might well be completed and the Spanish economy could run with a 100% renewable energy system by 2050, with requirements of sixteen and six times more installed capacity of solar-PV and wind onshore, respectively, by 2050 related to 2017.